Architecture at Scale: Reimagining One‐Off Projects as Building Platforms. (2nd March 2020) - Curtis, Craig
Abstract: The building industry is fraught with delays, lack of coordination on site and budget overruns. Craig Curtis, Head of Architecture and Interior Design at off‐site construction company Katerra, describes how his firm's fully integrated, reverse‐engineered, prefabricated housing units mitigate this.